PENGARUH EARNING PER SHARE, CURRENT RATIO, DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN PERIODE 2009-2015 - Aulia Heni Wijaya, 12.05.52.0091; Susilowati, Yeye (Students Journal of Accounting and Banking, 2017)
The study was to examines and analyzes the effect of earnings per share, current ratio and debt to equity ratio on stock price. This research was conducted at the Indonesian Stock Exchange by using a go public mining companies as the unit of analysis. The sampling method used purposive sampling with observation period from 2009 to 2015. Relationship and (or) influence between variable is described by using multiple regression analysis. The results showed that the earning per share and the current ratio has positive effect and significant to the stock prices. Whereas the debt to equity ratio had negative effect and significant on stock prices.Keywords:Â Earning Per Share, Current Ratio, Debt to Equity Ratio, and Stock Price